LEADERSHIP OF PRINCIPAL DEVELOPING LEARNING ORGANIZATION IN SD NEGERI BULUKANTIL SURAKARTA - Hidayah, Nenik (Universitas Sebelas Maret, 2018)
Technological developments require educational actors to keep learning in order to keep pace with technological developments. In order to maintain the quality and trust of the school institutions, then as an educational institution should be able to compete with schools and even with other non-formal institutions. This article is intended to describe the principal's leadership in implementing the school as a learning organization at SD Bulukantil Surakarta. The method that used in writing this article is qualitative research. The leadership of the principal at SD Negeri Bulukantil Surakarta has fulfilled five school requirements as a learning organization that includes personal skills, mental models, shared vision, team learning, and system thinking. The impacts of implementing learning organizations can be seen from the achievements of teachers, principals, learners and even school institutions. Learning organizations can be applied in other school institutions to improve their existence.